Helicopter Training Strategy: Study Case In Indonesia - Ichyu Machmiyana; Pangsa Rizkina Aswia; Andre Junifer (Langit Biru: Jurnal Ilmiah Aviasi, 2023)
External-load operation and instrument rating are important competencies for helicopter pilots to possess. This research was conducted with a descriptive qualitative approach. This article aims to find out the correct strategies for the education and training of helicopter pilots in Indonesia. Data collection techniques are through complete participatory observation, interviews with informants, and distributing questionnaires to civilian helicopter pilots. The results showed that the training programs were constrained by the very large helicopter operational costs for these activities. The results also showed that ownership of these competencies has a positive effect on helicopter pilots, both in carrying out external-load operations and when facing or trapped in instrument meteorological conditions (IMC). Based on the results of this research, helicopter pilot schools should conduct regular surveys of market needs, incorporate external-load operation syllabus and instrument ratings into education and training programs, as well as make improvements to the current training helicopters.